2018
DOI: 10.3389/fpsyg.2018.01805
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Investigation of the Interplay Among Professional Worth Appraisal, Self-Esteem and Self-Perception in Nurses: The Revelation of an Internal and External Criteria System

Abstract: Nurses’ professional self-concept is strongly associated with professional worth appraisal, which encompasses their feelings and perceptions regarding their task efficacy and value of input to clinical outcomes. Professional self-concept and professional worth appraisal are incorporated in one’s overall professional role perception. Data show that the way nurses think and feel about themselves personally and professionally, is associated with their well-being, the quality of provided patient care, their job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Furthermore, positive feelings about self and personal competencies seemed to enhance the perception of effectiveness in clinical settings and adequacy of professional skills, resulting in empowered professional identity and vice versa. 33 Austin et al also showed in their study that moral distress significantly influences the intention to leave work and quality of professional life. Thus, performing activities such as empowering nurses, focusing on leadership styles, providing opportunities for open discussion about ethical dilemmas, participating in policy-making with ongoing monitoring as well as assessing routine moral distress is guaranteed.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, positive feelings about self and personal competencies seemed to enhance the perception of effectiveness in clinical settings and adequacy of professional skills, resulting in empowered professional identity and vice versa. 33 Austin et al also showed in their study that moral distress significantly influences the intention to leave work and quality of professional life. Thus, performing activities such as empowering nurses, focusing on leadership styles, providing opportunities for open discussion about ethical dilemmas, participating in policy-making with ongoing monitoring as well as assessing routine moral distress is guaranteed.…”
Section: Discussionmentioning
confidence: 91%
“…55 On the same line, a qualitative study on Greek nurses revealed that the way nurses perceive themselves from the personal as well as the professional aspects, i.e., their professional identity, does influence their wellness feelings. 56…”
Section: Discussionmentioning
confidence: 99%
“…A lack of overwhelming support for animal research by society at large ( 30 ) can create workplace stress in research animal workers. Self-esteem and value are commonly tied to the nature of one's work ( 31 , 32 ) and the inability to speak about one's work to peers, friends or family members can contribute to feelings of discomfort and shame in research animal workers ( 4 ). Regularly communicating about the importance of the research being conducted can help to increase fluency in employees about the science.…”
Section: Factors Contributing To Workplace Stress In Animal Research mentioning
confidence: 99%